2011
DOI: 10.1111/j.1750-3841.2011.02193.x
|View full text |Cite
|
Sign up to set email alerts
|

Online Shear Viscosity Measurement of Starchy Melts Enriched in Wheat Bran

Abstract: Incorporation of wheat bran, a readily available and low cost by-product, in extruded puffed foods is constrained due to its negative effect on the product texture. Understanding the effect of wheat bran on rheological properties of extruded melts, driving the final product properties, is essential to provide solutions to the food industry and enhance its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…This is consistent with previous findings reported in the literature (e.g. Della Valle et al, 1996;Robin et al, 2011c). The decreasing effect of barrel temperature and water content can be explained by their plasticizing effect on the starch matrix.…”
Section: Effect Of Process Conditions On Shear Viscosity Of the Meltsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous findings reported in the literature (e.g. Della Valle et al, 1996;Robin et al, 2011c). The decreasing effect of barrel temperature and water content can be explained by their plasticizing effect on the starch matrix.…”
Section: Effect Of Process Conditions On Shear Viscosity Of the Meltsupporting
confidence: 92%
“…Regardless of the extrusion conditions, the melt showed a pseudoplastic behavior with a power law index n ranging from 0.14 to 0.29. These values were close to those reported by Robin et al (2011c) for extruded wheat flour supplemented with wheat bran. Increasing the barrel temperature, water content or screw speed significantly decreased the shear viscosity of the melt at a shear rate of 30 s À1 (Fig.…”
Section: Effect Of Process Conditions On Shear Viscosity Of the Meltsupporting
confidence: 91%
“…The rheological properties of the matrix surrounding the bubbles determine their resistance to growth. The shear viscosity of the melt was determined with the twin-slit rheometer at similar thermomechanical history of the ingredients as with the die (Robin et al, 2011b) and compared to the expansion data obtained with the same die. As the range of apparent shear rates achieved with the current rheometer (between 10 and 30 s À1 ) was much lower than the theoretical ones at the die exit (an apparent shear rate of about 600 s À1 would be expected), only the trends between the shear viscosity and the expansion will be discussed.…”
Section: Bulk Expansion and Cellular Structurementioning
confidence: 99%
“…However, the composition of the bran was not specified and the effect of bran on the flow behavior was not characterized. In a recent study, Robin et al (2011b) showed a significant effect of wheat bran on the melt shear viscosity of extruded wheat flour only at the highest wheat fiber concentration (24.4%), indicating a threshold bran volume fraction. Adding dietary fibers to the extruded melt may also modify the distribution of water between the different phases as shown in a previous work for unprocessed wheat flour supplemented with wheat bran (Robin et al, 2011a).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation